In vitro evaluation of fungicides and plant extracts against pathogenic fungi of two rice varieties - Chowdhury, Pranami; Bashar, MA; Shamsi, Shamim (Bangladesh Journal of Botany, 2018)
Five pathogenic fungi viz., Alternaria alternata (Fr.) Keissler, Curvularia lunata (Wakker) Boedijn, Drechslera oryzae Breda de Haan (Subramanian and Jain), Fusarium moniliforme Sheldon and Pestalotiopsis guepinii (Desm.) Stay. were isolated from two rice varieties viz., BRRI 29 (Boro) and Pajam (Aman) by Blotter and Tissue planting methods. Ten fungicides i.e. Bavistin 50 WP, Salcox 50 WP, Dithane M-45, Indofil M-45, Tall 25 EC, Ridomil MZ Gold, MC Sulphur 80, Greengel, Hayvit 80 WP and Capvit 50 WP at 100, 200, 300, 400 and 500 ppm were evaluated against the above mentioned five pathogenic fungi. Tall 25 EC completely inhibited the radial growth of the test fungi at all the concentrations except Fusarium moniliforme. Antifungal properties of ethanol extract of Artocarpus heterophyllus Lamk., Tagetes erecta L., Datura metel L., Senna alata (L.) Roxb., Azadirachta indica A. Juss., Citrus medica L., Mangifera indica L., Asparagus racemosus Willd., Nerium indicum Mill. and Allium sativum L. at 5, 10 and 20% concentrations were evaluated against the five test pathogens. All the plant extracts completely inhibited the radial growth of the test fungi at 20% concentration except Asparagus racemosus.